Can stories influence African-American patients' intentions to change hypertension management behaviors? A randomized control trial. Issue 9 (September 2016) - Bokhour, Barbara G.; Fix, Gemmae M.; Gordon, Howard S.; Long, Judith A.; DeLaughter, Kathryn; Orner, Michelle B.; Pope, Charlene; Houston, Thomas K.
Highlights: We studied the impact of a stories-based DVD to improve hypertension control. Stories DVDs were more engaging than DVDs with purely didactic information. Stories DVDs influenced African-American patients' intention to change behaviors. Stories DVDs are a scalable and effective way to use peer influence on health behaviors. Abstract: Objectives: Information-only interventions for hypertension management have limited effectiveness, particularly among disadvantaged populations. We assessed the impact of viewing African-American patients' stories of successfully controlling hypertension on intention to change hypertension management behaviors and engagement with educational materials. Methods: In a three-site randomized trial, 618 African-American Veterans with uncontrolled hypertension viewed an information-only DVD about hypertension (control) or a DVD adding videos of African-American Veterans telling stories about successful hypertension management (intervention). After viewing, patients were asked about their engagement with the DVD, and their intentions to change behavior. Mean scores were compared with two-sided t -tests. Results: Results favored the Stories intervention, with significantly higher emotional engagement versus control (4.3 vs. 2.2 p < 0.0001). Intervention patients reported significantly greater intentions to become more physically active (4.6 vs. 4.4, p = 0.018), use salt substitutes (3.9 vs. 3.4, p = 0.006), talk openly with their doctor about hypertension (4.6 vs. 4.5, p = 0.049), and remember to take hypertension medication (4.8 vs. 4.6, p = 0.04). Conclusion: Patients were more emotionally engaged and reported intentions to change behavior when watching real patient hypertension management success stories. Practice implications: Stories may be more influential than information alone, and represent a scalable approach to modifying behavioral intention.